Valoração econômico-ecológica dos serviços ecossistêmicos do manguezal na comunidade quilombola do Cumbe/Aracati - CE - Santos, Maria Miriam Barros dos (2024)
Coastal ecosystems play a crucial role by providing various ecosystem services directly impacting the economy and human well-being. Understanding the relationship between these ecosystems, the services they offer, and society is essential for developing effective policies for protecting and managing natural resources. In this context, the present study aims to investigate the environmental benefits of the mangrove ecosystem in the Quilombola Community of Cumbe, located in Aracati, Ceará. The focus is to assess the ecosystem services provided by this ecosystem, an area that faces constant threats to the well-being of its inhabitants, as well as significant environmental degradation due to the installation of large economic enterprises in the region. The methodology employed in the study consists of two main stages: the first involves classifying the ecosystem services according to the CICES (Common International Classification of Ecosystem Services) methodology, proposed by Haines-Young and Potschin (2009); the second focuses on valuing these services using the VERB (Estimated Reference Values for Environmental Benefits) methodology, based on the studies by Cardoso (2003) and Nascimento (2016). The results showed the identification of 21 ecosystem services, with a total average value of R$ 53,005,708.80, which corresponds to R$ 127,417.56 per hectare, considering an area of 416 hectares. Although various anthropogenic factors result in significant degradation of the ecosystem, the study highlights the mangrove's potential to provide essential environmental goods and services for the community. This research contributes to the body of studies in the field, enhancing the understanding of the relationship between humans and nature, as well as emphasizing the interdependence of natural resources, which are used both for income generation and subsistence. Furthermore, the research aims to contribute to the development of environmental public policies, considering the inclusion and perception of society regarding the environment in the decision-making process.